The Impact of Brand Image, Price, and Product Quality on Mobile Phone Purchase Decisions: A Quantitative Study: Dampak Citra Merek, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Ponsel: Studi Kuantitatif - Arif , Fikri Rohman; Indayani, Lilik (Indonesian Journal of Law and Economics Review, 2023)
This research investigates the influence of brand image, price, and product quality on consumers' decisions to purchase mobile phones at Top Sell Stores in Sidoarjo. Employing a quantitative approach with a sample of 100 consumers, multiple linear regression analysis, coefficient of determination (R2), t-test, F-test, and classical assumption tests were conducted using SPSS statistical software version 22. The findings reveal that brand image, price, and product quality individually exert a significant impact on mobile phone purchase decisions. Moreover, when considered together, they collectively influence consumers' choices. This study contributes to a deeper understanding of the factors shaping mobile phone purchasing behavior, offering valuable insights for businesses and marketers in optimizing their strategies to appeal to consumers in similar retail contexts. Highlights: Consumer Preferences: Examining the impact of brand image, price, and product quality on consumer choices in mobile phone purchases. Quantitative Analysis: Utilizing multiple linear regression and statistical tests to evaluate the significance of these factors. Practical Insights: Providing valuable insights for businesses and marketers to enhance their strategies in similar retail settings. Keywords: Brand Image, Price, Product Quality, Mobile Phone Purchase Decisions, Consumer Behavior